Association Between Physical Activity and Body Mass Index in Non-Insulin-Dependent Type 2 Diabetes Mellitus Patients - Yuliani, Kartika; Arsanti Lestari, Lily; Kertia, Nyoman (PROCEEDING SURABAYA INTERNATIONAL HEALTH CONFERENCE 2019, 2020)
For type 2 diabetes mellitus (T2DM) patients, lifestyle modification intervention including physical activity intervention is one of key points to improve BMI and other metabolic markers which can delay complications development. Nevertheless, modifying physical activity to meet recommendation is not easy. We tried to explore physical activity practice of T2DM patients from 3 public health services in Kota Yogyakarta and investigate the association between physical activity and body mass index. This study was a cross sectional study which conducted on 29 non-insulin-dependent type 2 diabetes mellitus patients. Physical activity was measured using IPAQ. The association between physical activity and body mass index was analyzed using Spearman’s Rank correlation test by STATA 13. Our study found that 96,55% participants had moderate and high level physical activity. The mean of participants BMI and IPAQ score were 27,13 ± 3,45 kg/m2 and 4463,94 ± 2324,19. The correlation between physical activity and body mass index was negative or protective (r = -0,02) but not significant (p=0,87). We suggest T2DM patients should not only do moderate or high physical activity but also do regular exercise and or maintain diet to achieve BMI improvement.